PENERAPAN INFORMASI AKUNTANSI PADA UMKM DI KECAMATAN SEKARBELA KOTA MATARAM - Awalia, Nailul; Yuliati, Ni Nyoman; Fauzi, Agus Khazin (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2018)
This study aims to examine the understanding of SMEs actors on accounting information and to know empirically the application of information for small and medium enterprises (MSMEs) in Sekarbela Subdistrict. This research used descriptive approach by interview and survey method. Data collection was done by distributing questionnaires to respondents. The sample of this research is food business MSMEs in Sekarbela Sub district with total of 68 UMKM. However, from 68 MSME samples only 50 samples can be processed. The data is processed by using the frequency distribution then made the average analysis and proportion. The results showed that MSMEs in Sekarbela Subdistrict have applied accounting information although in a simple form. Accounting information most widely applied is the purchase record with the number of 27 respondents or 54% and cash records 28 respondents or 56%. Then MSMEs in Sekarbela Subdistrict have used accounting information, the most widely used is the type of goods sold based on profit or profit of each type of goods with the number of 28 respondents or 56%. Furthermore, MSME also need operational information record about the number of goods sold per day with the number of 31 respondents or 62% and types of goods sold per day with the number of 31 respondents or 62%, records management information that is the production cost report with the number of 32 respondents or 64% financial information is the amount of profit each day with the number 46 respondents or 92%